Silk fibroin-based stretchable electronics - Cui, Yajing (Nanyang Technological University, 2021)
In this thesis, silk as an ancient commercial textile material has been successfully rendered with properties that meet the requirements for on-skin and implantable bioelectronics applications. Previously, instant water solubility, limited stretchability, and lack of suitable electronics fabrication methods are main factors that hindered the stable and wide application of silk material in soft bioelectronics. This thesis covers a complete process spanning from material modification, device fabrication to practical application of devices.